Impact of hydropower project (RoR) on the ichthyofaunal diversity of river Birahiganga in Central Himalaya (India) - Gurnam Singh; Naresh Kumar Agarwal (Journal of Fisheries, 2017)
We examined the present status of ichthyofaunal diversity of river Birahiganga in compliance to the construction of one hydropower project (HPP). The river is diverted through tunnel, leaving very less water in its fragmented course (~2.5 km). Sometime river gets almost dried in summer season. Altogether 20 fish species belonging to two orders, three families and eight genera were reported from fragmented and continuous flowing stretches of the river. Snow trout (Schizothorax and Schizothoraichthys spp.) have shown major share in total fish catch composition whereas the typical hill stream fishes (Garra and Pseudecheneis spp.) were the least contributor. Installation of HPP has effect on the fish population structure. Maximum species richness (20 species) was recorded from mainstream whereas 16 species were procured from the fragmented stretch. Relative abundance of most of the species was considerably high in the mainstream than the fragmented stretch, except Glyptothorax pectinopterus which has shown equal abundance at both the sites. Low water discharge in the fragmented stretch supports only small sized fishes. The degradation of habitat ecology and variation in physico-chemical features seems distressing the fish population structure.